Lissencephaly-A Brain Flawed - Manoj Mathur; Saryu Gupta (International Journal of Medical Research and Review, 2016)
We present a case report of a twelve-day old child suffering from seizures, in which magnetic resonance imaging (MRI) established the diagnosis of Lissencephaly. Although the causes of this disease entity are manifold, MRI can reveal stigmata of antenatal maternal infections in the child. In such a scenario, cytomegalovirus (CMV) is an important offender. In this article we discuss the pathogenesis of Lissencephaly in general, along with signs of transplacental CMV infection in the child. A diagnosis of CMV induced Lissencephaly obviates the need for chromosomal analysis and other genetic studies.